Implementasi Media Pembelajaran Berbasis Teknologi terhadap Motivasi Belajar - Arozatulo Bawamenewi; Riana Riana (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The learning process involves interaction between teachers and students to achieve effective and efficient educational goals. Learning media plays an important role in improving students' understanding and attracting their interest and attention to the material being taught. In today's digital era, the development of information and communication technology has made it possible to use various types of learning media, such as videos, animations, and interactive applications, which makes the learning process more interesting and enjoyable. This study aims to analyze internal and external factors that affect the effectiveness of the use of technology-based learning media on student learning motivation. The method used in this study is qualitative with a descriptive approach, involving students of the Indonesian Language and Literature Education study program. The results of the study show that the use of interactive learning media, especially videos, is very effective in improving students' understanding of concepts and stimulating their active involvement in the learning process. The availability of media that suits the needs of students and learning goals is essential to create a fun and productive learning atmosphere. The selection of the right learning media, based on student needs and learning objectives, can significantly improve the quality of education. The use of technology in education, especially technology-based media, provides opportunities to create a better learning experience, encourage student motivation, and achieve more optimal learning outcomes.